EFEKTIVITAS PENGGUNAAN MEDIA MONOPOLI MATEMATIKA DITINJAU DARI MINAT BELAJAR - pratiwi, arezky; Judrah, Muh; Irmayanti, Irmayanti (Math Educa Journal, 2023)
This study aims to determine the effectiveness of using monopoly mathematics media in terms of students' interest in learning mathematics. The type of research used in this research is a quasi-experimental type with nonequivalent control group design with a quantitative approach. This research was conducted at UPTD SMP Negeri 4 Sinjai. The population in this study were students of class VII UPTD SMP Negeri 4 Sinjai, totaling 91 people. The sample of this research is 60 people using purposive sampling technique. The results of the research based on the analysis of the Independent sample t-test results obtained a sig value of 0.000. The significance value is less than 0.05 or 0.000